Synthesis and charactherization of transition metal complexes with hydrazone schiff base ligands - Tang,, Suok Ing (University Malaysia Sarawak, UNIMAS., 2013)
The synthesis and spectroscopic characterization of two hydrazone Schiff base ligands(1-2) and their metal complexes Zn(C30H30N6O2), Co(C30H30N6O2), Fe(C30H30N6O2), Ni(C30H26N4O6), Zn(C30H26N4O6) & Fe(C30H26N4O6) (3-8) are reported in this thesis.Hydrazone Schiff base ligands 1 and 2 were obtained through the condensation reactions of 4-aminoacetophenone with benzhydrazide and 2’-hydroxyacetophenone with 4-hydroxybenzhydrazide respectively. The metal:ligand ratio is 1:2 for all complexes 3-8. The ligands experienced keto and enol tautomerization. The hydrazone Schiff base ligands (1-2) and their metal complexes (3-8) were characterized using FTIR, UV-Vis and 1H NMR spectroscopic studies. All hydrazone Schiff base ligands(1-2) and their metal complexes (3-8) are non-electrolyte in nature. Spectral studies suggested that hydrazone Schiff base ligand 1 acts as neutral bidentate ligand (N,O)whereas ligand 2 acts as a monoanionic bidentate ligand (N,O) towards central transition metal ions, and their metal complexes (3-8) were suggested to demonstrate a square planar geometry.